Hydra and the hair follicle – An unconventional comparative biology approach to exploring the human holobiont. (8th March 2022) - Lousada, Marta B.; Lachnit, Tim; Edelkamp, Janin; Paus, Ralf; Bosch, Thomas C. G.
Abstract: The microbiome of human hair follicles (HFs) has emerged as an important player in different HF and skin pathologies, yet awaits in‐depth exploration. This raises questions regarding the tightly linked interactions between host environment, nutrient dependency of host‐associated microbes, microbial metabolism, microbe‐microbe interactions and host immunity. The use of simple model systems facilitates addressing generally important questions and testing overarching, therapeutically relevant principles that likely transcend obvious interspecies differences. Here, we evaluate the potential of the freshwater polyp Hydra, to dissect fundamental principles of microbiome regulation by the host, that is the human HF. In particular, we focus on therapeutically targetable host‐microbiome interactions, such as nutrient dependency, microbial interactions and host defence. Offering a new lens into the study of HF – microbiota interactions, we argue that general principles of how Hydra manages its microbiota can inform the development of novel, microbiome‐targeting therapeutic interventions in human skin disease. Abstract : Microbial management in Hydra exhibits parallels to the human hair follicle. Therefore, these organisms provide an instructive model to study microbial regulation and interactions with the host that can be applied to study dysbiosis in hair follicle and hair follicle‐associated diseases research, by complete/targeted manipulation of the Hydra microbiome.